Ethnicity-specific myocardial remodelling in hypertensive heart disease by multi-parametric cardiovascular magnetic resonance. (3rd October 2022) - Mohamed, A T; Georgiopoulos, G; Faconti, L; Asher, C; Vennin, S; McNally, R; Vasileios, S; Alfakih, K; Lamata, P; Keehn, L; Chowienczyk, P; Masci, P G
Abstract: Background: Patients with systemic hypertension (HTN) of African ancestry (Afr-a) are at greater risk of incident heart failure (HF), hospitalisation and death than those of European ancestry (Eu-a). This has been related to higher prevalence of HTN-related target organ damage, including high level of circulating cardiac troponins, which is not fully explained by blood pressure level. Thus, one may speculate that Afr-a hypertensives have a higher tendency to develop myocardial damage in response to arterial afterload. However, myocardial composition differences between Afr-a and Eu-a hypertensives remain speculative. Purpose: To investigate ethnic-specific differences in myocardial tissue composition in Eu-a and Afr-a hypertensives by multi-parametric cardiovascular magnetic resonance (CMR). Methods: This cross-sectional study included 63 Afr-a and 47 Eu-a hypertensive patients. All patients underwent multi-parametric CMR (1.5-Tesla Aera, Siemens-Healthcare, Erlangen-Germany). Left (LV) and right ventricular (RV) volumes, mass and function, atrial dimensions, and myocardial tissue characterisation (including T1- and T2-mapping) were measured using a standardised imaging protocol, and post-processing recommendations from international scientific societies. Analysis was completed using a commercially available cardiac-software (CVI-42, Calgary-Canada). Central pulse-wave-velocity (PWV) between the ascending and proximal descending thoracic aorta was measured by high-temporal, resolution 2D phase-contrast velocity-encoded parasagittal cine images, using in-house MATLAB software. Results: Although Afr-a were 5 years older than Eu-a hypertensives, cardiovascular risk factors, anthropometric, body composition and haemodynamic measures were similar between the two groups (Figure 1). Segmental PWV was greater in Afr-a than Eu-a patients (8.16±2.71 vs 6.97±2.82 m/s, P=0.044), underlying higher aortic stiffness in Afr-a hypertensives. Afr-a hypertensives also had greater LV mass and LV-mass/end-diastolic volume ratio than Eu-a (Figure 2), whilst no difference was observed in LV systolic/diastolic function. Native T1 relaxation time and synthetic extracellular volume were also similar between the two ethnicities, though T2 relaxation time was significantly higher in Afr-a hypertensives. Late gadolinium enhancement (LGE), a well-established metric of replacement fibrosis (scarring), was more prevalent in Afr-a than Eu-a hypertensives (14% vs 4%, P=0.001). In patients with LGE, the extent of LGE was higher in Afr-a than Eu-a hypertensives (Figure 2). Conclusion: Afr-a hypertensives have higher arterial afterload, LV mass and remodelling than Eu-a, despite comparable mean blood pressure, body-mass-index, and body composition. These changes in LV structure and geometry were associated with higher T2 relaxation time, likely reflecting low-grade inflammation, as well as higher prevalence and extent of replacement myocardial fibrosis. Funding Acknowledgement: Type of funding sources: None.